Paradiplomasi Jawa Barat dalam Pengembangan Bandung Green Smart City melalui Proyek ODA Chungcheongnam-do - Hisyam, Muhammad Hauzan; Azmi, Fuad (Global Political Studies Journal, 2025)
As a key cooperation partner of the Republic of Korea, Indonesia has long been a target of Korean Official Development Assistance (ODA) projects. Aligning with West Java's long-term plan to develop Bandung Green Smart City, Chungcheongnam-do, a province in Korea; through the Chungnam Center for Creative Economy and Innovation (CCEI), offered grant assistance to develop electric public transportation infrastructure through a knowledge-sharing-based ODA scheme. As a response, a series of prolonged diplomatic agendas were carried out to maximize the interests of each party. Based on qualitative research design, this article reveals the strategic maneuvers of the West Java Government's paradiplomacy in the project by examining paradiplomacy approaches, such as dialogue, negotiation, compromise, and lobbying, which can be identified through various cooperation agendas, especially meetings, field visits, and working groups. It is concluded that the paradiplomacy agenda is dominated by the West Java Provincial Government, emphasizing a peaceful approach and collaborative strategies with mutual respect for common interests, resulting in diplomatic outputs that primarily include regional economic acceleration. The presence of this article complements the literature on regional paradiplomacy in Indonesia to be further studied through ODA projects, thus initiating a more specific exploration of discussions beyond just twin cities. Keywords—CCEI, ODA Project, Paradiplomacy, West Java